Effects of step movement on the starting block with a back plate for start performance in competitive swimming relay start - Suzuki, T.; Komatsu, T.; Tsunokawa, T.; Mankyu, H.; Maeda, A. (Japanese Journal of Sciences in Swimming and Water Exercise, 2020)
The purpose of the present study was to evaluate the effectiveness of different step movement of relay starts with a back plate in competitive swimming. Twelve elite swimmers performed three different types of relay start and Kick Start. The start motions were recorded by six video cameras, and the 3D-DLT method was used to calculate the kinematic variables. As a result, there were no significant difference for male swimmers in the variables related to velocity and angle between No-Step and Single-Step, but the Advanced-Step attained a higher horizontal velocity at take-off. In female swimmers, there was no difference in all relay starts. In addition, Advanced-Step did not exceed the performance of the Kick Start. This fact shows that swimmers don't make the advantage that they don't have to make a pause in a relay start.